The association between closed-eye unipedal standing and the risk of cognitive impairment in the elderly: a 7-year community-based cohort study in Wuhan, China - Wang, Shiwei; Guo, Peng; Huang, Chengjing; Zhang, Yuqian; Xiang, Bing; Zeng, Jing; Zhou, Feng; Xie, Xinyan; Guo, Yan; Yang, Mei (Frontiers in Aging Neuroscience, 2024)
The prevention of cognitive impairment in elderly is one of the public health priority areas. However, the relationship between closed-eye unipedal standing and cognitive impairment is unclear.This was a community-based prospective elderly cohort study. Participants were followed for 7 years and diagnosed with new-onset cognitive impairment. Logistic regression models and restricted cubic spline (RCS) were used to investigate the relationship between closed-eye unipedal standing and cognitive impairment. Stratified analysis by baseline characteristics were also performed.Results: 1652 people ≥ 65 years of age were enrolled at baseline, and 880 participants ultimately completed follow-up, 155 (17.61%) participants satisfied the diagnostic criteria for cognitive impairment at follow-up. Taking the closed-eye unipedal standing low group as the reference, the cognitive impairment risks in middle (OR=0.601, 95% CI:0.396-0.911) and high (OR=0.508, 95% CI:0.329-0.785) groups were significantly lower. And RCS suggested a linear relationship (P non-linear = 0.177), with a reduced risk of developing cognitive impairment when the duration of closed-eye unipedal standing was higher than approximately 2.920 seconds. Stratified analysis showed that for female, ≤70 years old, with ≥3 years of education, without lack of exercise and without falls within 1 year subgroup, the elderly with the high group of closed-eye unipedal standing had significantly reduced cognitive impairment risks.In the elderly, closed-eye unipedal standing duration was linearly and negatively associated with cognitive impairment risk. The closed-eye unipedal standing duration might be a predictive index for cognitive impairment in the elderly.